P11. Connectivity-based predictions of hand motor outcome at the sub-acute stage after stroke. Issue 8 (August 2015) - Lindow, J.; Domin, M.; Grothe, M.; Byblow, W.; Lotze, M.
<x xml:space="preserve">Abstract</x> Predicting motor recovery after stroke is a recognized aim in stroke rehabilitation. Here, we combine two different neuroimaging methods to test their prognostic power at the sub-acute stage after stroke. We measured resting state fMRI (rs-fMRI) and diffusion weighted imaging (DWI) in 19 stroke patients within the first days (5–9 days) after stroke and investigated short term (3 months) and long term (6 months) motor outcome. Resting-state functional connectivity (rs-FC) showed no relevant predictive value for motor outcome. We found trends for negative associations between the rs-FC of primary motor cortex (M1) of the lesioned hemisphere and dorsal premotor cortices (dPMC) of the contralesional side with grip force of the affected upper limb at 3 months. In addition, a poorer short-term outcome for pinch grip performance was associated with rs-FC of M1 and the supplementary motor area (SMA) in the lesioned hemisphere. In contrast DWI showed a predictive value for both short-term and long-term motor outcome. Integrity along the M1-pons tract showed good predictive value for a positive outcome at 6 months. Overall, structural connectivity measures derived from probabilistic DWI may offer better prognostic information than rs-fMRI at the early phase after stroke.